Evaluation of Differences in Patient and Physician Perception of Benefit and Risks of Aspirin and Antifibrinolytic Therapy in Cardiac Surgery. Issue 5 (September 2014) - Myles, P. S.; Thompson, G.; Fedorow, C.; Farrington, C.; Sheridan, N.
It is unclear whether physicians and patients have similar concerns and preferences when considering benefit and risks of aspirin and antifibrinolytic therapy for cardiac surgery. We surveyed both groups to ascertain their perceptions and preferences for treatment in this setting. Both preoperative and postoperative cardiac surgical patients and the physician craft groups caring for them (cardiology, surgery, anaesthesia/critical care), were provided with estimates of benefits and risks of aspirin and antifibrinolytic therapy. All study participants were asked to stipulate the minimal absolute risk reduction required for them to agree to such therapy. When compared with the cardiac surgical patients they treat, physicians required a smaller thrombotic risk reduction with aspirin whilst accepting its known increased risk of bleeding. This was significantly different in a high-risk stroke setting (incidence 5%) where the required relative risk reduction with aspirin use for physicians was 20% versus patients 40% ( P <0.001); and for myocardial infarction, physicians 20% versus patients 36% ( P =0.051). For antifibrinolytic therapy, the tolerated increased relative risk of stroke for physicians was 20% versus patients 10% ( P =0.004), and for myocardial infarction, physicians 16.7% versus patients 4.2% ( P <0.001). The three physician craft groups had comparable tolerances of thrombotic risk. Patient and physician preferences for perioperative aspirin and antifibrinolytic therapy sometimes differ based on risk benefit analysis.